Pemanfaatan Media Sosial Instagram Koalisi Pemuda Hijau Indonesia (KOPHI) Sebagai Media Publikasi Kegiatan - Wasono Adi; Handini Prabawati (Communicology: Jurnal Ilmu Komunikasi, 2019)
Abstract Koalisi Pemuda Hijau Indonesia (KOPHI), a community engaged in the environment, often discusses issues and phenomena that occur at that time. In carrying out their activities, Media and Communication (MedCom) team utilized instagram social media as a media publication activity, descriptive study: on the instagram account @_kophi. However, the low instagram engagement is an obstacle in gaining feedback from followers. The purpose of this study is to find out how to use instagram @_kophi social media throught several stages of share, manage, optimize, and manage. This research uses the main theory of social media namely The Circular Model of SoMe from Regina Luttrell. This study used a descriptive qualitative method and this study contained 3 key informats and 5 informants in this study. The results showed that at the share stage, the instagram social media chosen by KOPHI community was appropriate. In the optimize stage, the use of instagram @_kophi is quite optimal but KOPHI does not have a spacific strategy in developing its instagram account. At the manage stage, to carry out media monitoring KOPHI community uses Insight Instagram Analytics. At the engage stage, it is known that KOPHI Instagram followers do not always actively follow KOPHI Instagram developments and rarely respond to KOPHI Instagram posts. KOPHI community continues to optimize the use of the Instagram feature to support publication on their Instagram accounts. Keywords: Koalisi Pemuda Hijau Indonesia (KOPHI), Instagram, The Circular Model of SoMe